Cine Forum and Criticism: necessary encounter - Calopiña, Milton (2022)
The present work examines some of the possibilities of an encounter between two activities apparently related, but that actually follow a way different, the critic of cinema and the Cinema Forum. Both make analysis of films, but under different parameters and also persecute different objectives. Nevertheless a closer relationship between both could be important. For it we were based on experiences of the author and other people, made in different places and diverse moments, as well as the opinion of different authors, nationals and foreigners on the subject.